Two-inch high-quality (001) diamond heteroepitaxial growth on sapphire (112̄0) misoriented substrate by step-flow mode. (5th October 2021) - Kim, Seong-Woo; Takaya, Ryota; Hirano, Shintaro; Kasu, Makoto
Abstract: Two-inch-diameter high-quality free-standing (001) diamond layers were grown on misoriented (11 2 ̄ 0) sapphire. The substrate misorientation allows step-flow growth, and tensile stress is released in the diamond layer. Consequently, the diamond layer delaminates naturally from the substrate without cracking. For the diamond grown on the sapphire misoriented by 7° toward the [1 1 ̄ 00] direction, the widths of the (004) and (311) X-ray rocking curves were 98.35 and 175.3 arcsec, respectively, the lowest ever reported. The curvature radius of the diamond was 99.64 cm in the [1 1 ̄ 00] direction and 260.21 cm in the [0001] direction of the substrate, the highest ever reported.